Recovery trajectories of mental health symptoms among Chinese adolescents following the end of COVID-19 - Peng, Jun; He, Meihui; Guo, Yongxing; Diao, Jiangdong; Chen, Kun; Deng, Ziyi; Mo, Lei; Gao, Ruixiang (Frontiers in Public Health, 2024)
BackgroundThe COVID-19 pandemic has had a profound impact on global mental health, particularly among adolescents. However, little is known about how mental health symptoms recover after the pandemic subsides. This study aims to examine the recovery trajectories of ten mental health problems and suicidal ideation among Chinese adolescents post-pandemic, with a focus on identifying factors that influence different recovery patterns.MethodsA total of 2,534 adolescents participated in a three-wave survey, conducted in June 2022, November 2022, and March 2023, using the Mental Health Scale for Chinese Middle School Students. A novel index was developed to account for both the number and severity of mental health risk factors, allowing for the classification of psychological symptoms into three subgroups: no, moderate, and severe. Polynomial regression models were applied to determine the acceleration inflection point, and multivariate logistic regressions identified predictors of trajectory membership.ResultsSignificant declines in psychological symptoms were observed. Seven trajectory patterns were identified: resistance (37.85%), recovery (22.61%), chronic-dysfunction (12.08%), aftermath-deterioration (10.81%), stress-responsiveness (8.21%), vulnerability (5.76%), and remitting (2.68%). Being female, senior high school students, and the oldest child in the family hindered mental health recovery, whereas parenting styles of companionship, empathetic support, promise fulfillment, and behavior intervention served as protective factors.ConclusionThis study is one of the first to reveal the post-pandemic mental health recovery trajectories of Chinese adolescents, highlighting the importance of considering both the number and severity of cumulative mental health problems. The findings offer valuable insights into suicide prevention and the development of targeted interventions to support youth mental health recovery.